FAKTOR YANG MEMPENGARUHI PORSI PEMBIAYAAN BAGI HASIL (STUDI PADA BANK PEMBIAYAAN RAKYAT SYARIAH DI DIY DAN JAWA TENGAH) - Setya Pramono; Ari Widayati (Journal Competency of Business, 2019)
This study examines conceptual and empirical models regarding Manager Skills, Sharia Compliance, Characteristics of Islamic Banks, Manager's Perceptions of Islamic Bank Internal SDI, Manager's Perceptions of Customer Characteristics, Manager's Perceptions of the Existence of Regulation, Manager's Perceptions of Government Support for the Portion of Profit Sharing Financing in Sharia People's Financing Bank The selection of research locations was carried out by means of a simple random proportional technique (proportional simple random sampling). The sampling technique used in this research was purposive sampling. In this study there were 36 BPRS in DIY and Central Java, then five people were taken as respondents for each BPRS consisting of the Board of Directors, the Sharia Supervisory Board, Marketing Manager, Operations Manager (Financing Manager) and Customer Service. So the number is 180 (one hundred and eighty) respondents. As for the object of the assessment is the Operations Manager / Funding Manager, considering that this research is related to the portion of profit sharing financing. The results showed that 1) Manager's conceptual skills had a positive effect on the portion of profit-sharing financing in BPR Syariah 2) Manager's technical skills had a positive effect on the portion of profit-sharing financing in BPR Syariah 3) Manager's social skills had a positive effect on the portion of profit-sharing financing in BPR Syariah 4 ) Managers' perceptions about the internal SDI of Islamic banks have a positive effect on the portion of profit-sharing financing in Islamic BPR Sharia BPR 7) There is no influence of the characteristics of Islamic banks on the portion of profit sharing financing in Sharia BPR 8) There is no effect of sharia compliance on the portion of profit sharing financing in Islamic BPR face the portion of profit sharing financing in Sharia BPR